Synchronous Foreignicity:: Fred Wah’s Poetry and the Recuperation of Experimental Texts - Weaver, Andy (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2005)
Fred Wah challenges the binary opposition implicit in the postmodern idea that, as experimental texts expose and explode the artificiality of accepted norms, they are soon recuperated into the mainstream. Wah's theory of synchronous foreignicity privileges neither the reified/modern nor the vital/postmodern; by inclusively pairing the conventional and the radical, it places both author and reader in the "and" or the "hyphen" between binaries. Wah does not identify with any one ethnic group, enabling him to draw from multiple perspectives. His sequence "Music at the Heart of Thinking" exemplifies his notion of synchronous foreignicity. The formal changes defamiliarize the familiar in order to break down reified thoughts and perception without obliterating them. The text itself is both old and new, modern and postmodern, conventional and radical, provoking the reader to an evolution, rather than revolution, in thought.